2011
DOI: 10.1063/1.3605542
|View full text |Cite|
|
Sign up to set email alerts
|

Tailoring magnetic anisotropy in epitaxial half metallic La0.7Sr0.3MnO3 thin films

Abstract: We present a detailed study on the magnetic properties, including anisotropy, reversal fields, and magnetization reversal processes, of well characterized half-metallic epitaxial La 0.7 Sr 0.3 MnO 3 (LSMO) thin films grown onto SrTiO 3 (STO) substrates with three different surface orientations, i.e., (001), (110), and (118). The latter shows step edges oriented parallel to the [110] (in-plane) crystallographic direction. Room temperature high resolution vectorial Kerr magnetometry measurements have been perfor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
48
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 38 publications
3
48
0
Order By: Relevance
“…12,13 Moreover, by using vicinal surfaces we can fabricate artificially periodic stepped surfaces with in-plane magnetic anisotropy. 14 In vicinal substrates, the surfaces are intentionally misoriented to a (near) low index surface, therefore determining surface step edges. In such a way, the high symmetry of the low index surface is broken and an additional uniaxial anisotropy is expected.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…12,13 Moreover, by using vicinal surfaces we can fabricate artificially periodic stepped surfaces with in-plane magnetic anisotropy. 14 In vicinal substrates, the surfaces are intentionally misoriented to a (near) low index surface, therefore determining surface step edges. In such a way, the high symmetry of the low index surface is broken and an additional uniaxial anisotropy is expected.…”
mentioning
confidence: 99%
“…The vicinal angle h v was from the [001] surface toward the ½1 10 crystallographic direction, thus inducing step edges along the ½110 direction. 14 The laser fluence was 1-2 J cm À2 , the target-to-substrate distance, the oxygen pressure, and the substrate temperature were optimized to 50 mm, 0.35 mbar, and 720 C, respectively. 9 The crystal structure was investigated by means of x-ray diffraction (XRD).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Different magnetic anisotropies could be induced in the LSMO films depending on the substrate type, as previously shown in [4]. The magnetoresistance versus magnetic field in the case of a stripe patterned in a 50 nm thick LSMO film deposited on STO (001) and aligned at 45° with respect to the easy axis direction is shown in Figure 2.…”
Section: Magnetoresistance and Low Frequency Noise Measurementsmentioning
confidence: 83%
“…Previous studies have noted both uniaxial and biaxial anisotropies present in STO/LSMO films, with the biaxial anisotropy originating from the cubic symmetries of epitaxial LSMO grown on (001) STO and the uniaxial anisotropies originating from physical steps on the STO surface [13,[34][35][36]. It was reported that the in-plane fourfold and two-fold anisotropies are bulk in origin and not strongly related to interface pinning.…”
Section: Fmr Results and Discussionmentioning
confidence: 99%